2021
DOI: 10.3928/23258160-20210528-04
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Endophthalmitis Associated With Intravitreal Injection of Anti-VEGF Agentsat a Tertiary Referral Center

Abstract: BACKGROUND AND OBJECTIVE: To report the incidence and clinical features of infectious endophthalmitis after intravitreal (IV) injection of anti-vascular endothelial growth factor inhibitors (VEGF) between 2018 and 2020 and to compare to prior rates. PATIENTS AND METHODS: Retrospective analysis of patients with endophthalmitis after anti-VEGF IV injections treated at Bascom Palmer Eye Institute between January 1, 2018, and December 31, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
2
14
0
3
Order By: Relevance
“…The incidence of endophthalmitis in our study differed in comparison with the findings reported in previous studies, which seems to be mainly related to differences in study design, patient characteristics, and the definition of endophthalmitis. In a 2-year single-center retrospective study, the incidence of clinically diagnosed endophthalmitis was reported to be 0.014%, which is consistent with our study [ 12 ]. However, another 4-year multicenter retrospective study found that the incidence of presumed infectious endophthalmitis was much higher (0.04%) [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The incidence of endophthalmitis in our study differed in comparison with the findings reported in previous studies, which seems to be mainly related to differences in study design, patient characteristics, and the definition of endophthalmitis. In a 2-year single-center retrospective study, the incidence of clinically diagnosed endophthalmitis was reported to be 0.014%, which is consistent with our study [ 12 ]. However, another 4-year multicenter retrospective study found that the incidence of presumed infectious endophthalmitis was much higher (0.04%) [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a study using US claims data, the incidence of antibiotic-associated endophthalmitis was higher with aflibercept than with ranibizumab (0.44% vs. 0.22%), and the risk of developing endophthalmitis was also higher with aflibercept (adjusted relative ratio, 2.04; 95% CI, 1.42–2.92; p < 0.05) [ 14 ]. However, some studies showed no statistically significant differences in the incidence of endophthalmitis by medication type [ 12 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Die Inzidenz der postoperativen Endophthalmitis (ohne intravitreale Injektionen) wird zwischen 0,05 % und 0,09 % angegeben [1,2]. Die Endophthalmitisrate nach intravitrealer Injektion liegt zwischen 0,008 % und 0,077 % [3,4]. Aufgrund der hohen Anzahl an Kataraktoperationen und intravitrealen Injektionen beobachtet man eine Endophthalmitis postoperativ hier zahlenmäßig häufiger, auch wenn der prozentuale Anteil (Kataraktoperation: 0,04 % bzw.…”
Section: Endophthalmitis Aus Ophthalmopathologischer Sichtunclassified
“…Aufgrund der hohen Anzahl an Kataraktoperationen und intravitrealen Injektionen beobachtet man eine Endophthalmitis postoperativ hier zahlenmäßig häufiger, auch wenn der prozentuale Anteil (Kataraktoperation: 0,04 % bzw. 0,08 % [1,2]; intravitreale Injektionen 0,014 % [3]) unter der Inzidenz derer bei perforierender Keratoplastik (0,08 % bzw. 0,178 % [1,2]) und Glaukomoperationen (0,2 % bzw.…”
Section: Endophthalmitis Aus Ophthalmopathologischer Sichtunclassified
See 1 more Smart Citation